Vaccines and global health - Greenwood, B; Salisbury, D; Hill, A (2011)
Vaccines have made a major contribution to global health in recent decades but they could do much more. In November 2011, a Royal Society discussion meeting, 'New vaccines for global health', was held in London to discuss the past contribution of vaccines to global health and to consider what more could be expected in the future. Papers presented at the meeting reviewed recent successes in the deployment of vaccines against major infections of childhood and the challenges faced in developing vaccines against some of the world's remaining major infectious diseases such as human immunodeficiency virus (HIV), malaria and tuberculosis. The important contribution that development of more effective veterinary vaccines could make to global healthwas also addressed. Some of the social and financial challenges to the development and deployment of newvaccineswere reviewed. The latter issueswere also discussed at a subsequent satellite meeting, 'Accelerating vaccine development', held at the Kavli Royal Society International Centre. Delegates at this meeting considered challenges to the more rapid development and deployment of both human and veterinary vaccines and howthese might be addressed. Papers based on presentations at the discussion meeting and a summary of the main conclusions of the satellite meeting are included in this issue of Philosophical Transactions of the Royal Society B. © 2011 The Royal Society.